The status of occasional benefits within Social Assistance Policy: some notes - Santos, Vera Núbia; Gonçalves, Maria da Conceição Vasconcelos; Sales, Ana Carolyna Ribeiro (Argumentum, 2025)
This article reflects on occasional benefits within Social Assistance Policy, problematising the main challenges to their implementation from a rights perspective. It employs bibliographic research and documentary sources from a survey available on the World Wide Web, based on historical-dialectical materialism. It concludes that the trajectory of occasional benefits has faced obstacles related to their definition, regulation, and funding, and that this has hindered their achievement as a social right.